The Role of Inhaled Chitosan-Based Nanoparticles in Lung Cancer Therapy - Allana Carvalho Silva; Mirsiane Pascoal Costa; Thiago Medeiros Zacaron; Kézia Cristine Barbosa Ferreira; Wilson Rodrigues Braz; Rodrigo Luiz Fabri; Frédéric Jean Georges Frézard; Frederico Pittella; Guilherme Diniz Tavares (MDPI AG, 2024)
Lung cancer is the leading cause of cancer-related mortality worldwide, largely due to the limited efficacy of anticancer drugs, which is primarily attributed to insufficient doses reaching the lungs. Additionally, patients undergoing treatment experience severe systemic adverse effects due to the distribution of anticancer drugs to non-targeted sites. In light of these challenges, there has been a growing interest in pulmonary administration of drugs for the treatment of lung cancer. This route allows drugs to be delivered directly to the lungs, resulting in high local concentrations that can enhance antitumor efficacy while mitigating systemic toxic effects. However, pulmonary administration poses the challenge of overcoming the mechanical, chemical, and immunological defenses of the respiratory tract that prevent the inhaled drug from properly penetrating the lungs. To overcome these drawbacks, the use of nanoparticles in inhaler formulations may be a promising strategy. Nanoparticles can assist in minimizing drug clearance, increasing penetration into the lung epithelium, and enhancing cellular uptake. They can also facilitate increased drug stability, promote controlled drug release, and delivery to target sites, such as the tumor environment. Among them, chitosan-based nanoparticles demonstrate advantages over other polymeric nanocarriers due to their unique biological properties, including antitumor activity and mucoadhesive capacity. These properties have the potential to enhance the efficacy of the drug when administered via the pulmonary route. In view of the above, this paper provides an overview of the research conducted on the delivery of anticancer drug-loaded chitosan-based nanoparticles incorporated into inhaled drug delivery devices for the treatment of lung cancer. Furthermore, the article addresses the use of emerging technologies, such as siRNA (small interfering RNA), in the context of lung cancer therapy. Particularly, recent studies employing chitosan-based nanoparticles for siRNA delivery via the pulmonary route are described.